Multidrug Resistant E-Coli in Patients with Urinary Tract Infections Presenting to Internal Medicine Clinics of Two Tertiary Care Hospitals in Lahore, Tip of the Iceberg - Rana, Muhammad Asim; Siddiqui, Mujtaba Hasan; Ahmad, Atiq; Qayyum, Mohammad Ahad; Iqbal, Waseem; Iqbal, Javeid; Hafeez, Muhammad Mansoor; Asif, Sonia; Zaka, Hira (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The commonly presenting infections in medical outpatients’ department are that of Urinary tract. If not treated properly these can lead to hospitalization and can increase the morbidity and mortality. Escherichia coli is found to be the most frequent bacterium causing these infections. The available literature may not under representing the prevalence of E. Coli which is multi drug resistant and is seen in general medical outdoor and internal medicine clinics of our local population, because urine sample is usually sent for culture only in complicated patients. Objective: To determine the prevalence of multi drug resistant E. Coli and its resistance to the most commonly used antimicrobial agents in Internal Medicine Clinics of Bahria International Hospital, and Farooq Hospital, West wood branch, Lahore. Study Design: This is an observational study done retrospectively carried out at Internal Medicine Clinics of Bahria International Hospital Lahore and Farooq Hospital, Lahore from 1st January 2019 to 31st December 2020. Methodology: One hundred and ninety adult patients with urinary symptoms and suspected UTI were enrolled. We analyzed the available urine culture reports and susceptibility against the pathogens. The testing was interpreted according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) standards. Results: The most common microorganism was E. Coli (70%) followed by klebsiella (17.9%), enterococcus (8.9%) and Acinetobacter (3.2%) in both complicated and uncomplicated urinary tract infections. 75 % females were E. coli positive as compared to the male (58.6%). Patients aged greater than 60 and less than 20 years were mostly affected with E. coli. Most of the isolated pathogens were highly resistant to ampicillin, cotrimoxazole, and cephalexin (70%–95.5%). Conclusion: E. coli is found highly resistant to antimicrobial agents used to treat UTI at family medicine practice. No difference could be appreciated in the apportioning of resistant E. coli in both complicated and uncomplicated UTIs. This study emphasizes that we should collect data at National level and prepares a proper guideline for choosing appropriate antibiotics in patients with UTI presenting to general medical clinics.